Implementasi Program Smart Inclusive School (SIS) - Nabilah Dini Ramadhani; Ertien Rining Nawangsari (Univiversitas Dr. Djar Wattiheluw, 2023)
SMPN 28 Surabaya is one of the inclusive education providers that provide innovative Smart Inclusive School (SIS) programs. However, the implementation of the SIS program is still constrained by unsupportive infrastructure and inadequate teacher competence so the implementation of SIS program is not optimal. This study aims to look at the implementation of SIS program at SMP Negeri 28 Surabaya using David C. Korten's program implementation suitability model in which 3 elements are, the programs, implementing organizations, and target groups. In the program element, the implementation of Smart Inclusive School has been well understood and implemented by the school as well as PDBK and parents. the implementing organization element, namely regular teachers and special assistants, has been equipped with training so that there is an understanding of handling Peserta didik berkebutuhan khusus (PDBK). The target group element, namely PDBK and parents, has benefited from the Smart Inclusive School program, although there are still obstacles in adapting the environment for PDBK.